Effect of beam offset on the microstructure and mechanical properties of 201SS-Q235 self-fusion LBW joint. (November 2019) - Jiang, Xizhi; Du, Chengchao; Ni, Mansheng; Liu, Junjian
Abstract: The 201SS and Q235 plates were joined using self-fusion LBW joint with different beam offset. The results showed that more 201SS in the FZ when the beam was shifted from Q235 side to 201SS side contributed to the more RA and δ -Fe phase. The twinned martensite was observed in the FZ containing 201SS with a volume fraction of 60.5% (the FZ was called "FZ-3″). The tensile test of joint showed that the fracture occurred in the Q235 BM. The tensile test and impact test of sub-sized samples showed that more 201SS in the FZ declined the strength, plasticity, and toughness. The remarkable compressive stress was observed in WD as the volume increase from the MT of FZs during the cooling stage. The volume increase of FZ declined gradually as the increase of 201SS in it. The smallest volume increase of FZ-3 contributed to its lowest compressive stress in WD.